Does Magic Offer a Cryptozoology Ground for Psychology?. Issue 2 (June 2015) - Thomas, Cyril; Didierjean, André; Maquestiaux, François; Gygax, Pascal
Magicians often trick spectators' senses by relying on cognitive limitations. To do so, they use intuitive but age-old knowledge of human cognition. Research into the relationship between magic and psychology has been growing for a number of years now. This work offers an original ground for studying cognitive processes, while also providing the opportunity to discover processes that are still poorly understood. In this respect, the study of magic in psychology resembles the domain of "cryptozoology, " the name given to the search, real or humoristic, for unknown species. This article begins by briefly presenting some of the major research conducted over the past 10 years in the psychology of magic. We argue that, unfortunately, so far, no unknown cognitive species have been added to the "hunting bag" of these studies; in the second part of the article, we discuss the wide range of psychological facets of magic that are still to be explored.